Adaptation Atlas Notebook: Estimate economic returns on adaptation / Estimer les retours économiques de l’adaptation - Steward, Peter; Youngberg, Brayden; Thornton, Philip Kenneth; Muller, Lolita; Rosenstock, Todd (2025)
This notebook provides an interactive tool to estimate the economic returns of climate adaptation practices in African agriculture. It combines evidence on adoption costs, productivity impacts, and climate-information benefits to calculate net cash flows for different adaptation interventions. Users can adjust assumptions and explore how outcomes vary by practice type and impact pathway. By summarizing both annual and cumulative economic returns, the notebook helps policymakers, investors, and practitioners identify which adaptation actions deliver the strongest financial benefits for farmers and where investment is most likely to pay off.